Diversity of the subspecies Bifidobacterium animalis subsp. lactis - Bunesova, Vera; Killer, Jiri; Javurkova, Barbora; Vlkova, Eva; Tejnecky, Vaclav; Musilova, Sarka; Rada, Vojtech (Anaerobe, 2017)
Strains of Bifidobacterium animalis subsp. lactis are well-known health-promoting probiotics used commercially. B. animalis subsp. lactis has been isolated from different sources, and little is known about animal isolates of this taxon. The aim of this study was to examine the genotypic and phenotypic diversity between B. animalis subsp. lactis strains different animal hosts including Cameroon sheep, Barbary sheep, okapi, mouflon, German shepard and to compare to BB12, food isolates and the collection strain DSM 10140. Ten strains of B. animalis subsp. lactis from different sources were characterised by phenotyping, fingerprinting, and multilocus sequence typing (MLST). Regardless of origin, MLST and phylogenetic analyses revealed a close relationship between strains of B. animalis subsp. lactis with commercial and animal origin with the exception of isolates from ovine cheese, mouflon and German Shepard dog. Moreover, isolates from dog and mouflon showed significant differences in fermentation profiles and peptide mass fingerprints (MALDI-TOF). Results indicated phenotypic and genotypic diversity among strains of B. animalis subsp. lactis.
Keywords: fenotyp; Phenotype; Molecular Typing; Mammals; genetická variace; Genotype; fylogeneze; techniky typizace bakterií; Phenotyping; Environment; Phylogeny; Bifidobacterium animalis; Origin; potravinářská mikrobiologie; savci; Animals; Food Microbiology; zvířata; Bifidobacteria; Genotyping; spektrometrie hmotnostní - ionizace laserem za účasti matrice; molekulární typizace; Bacterial Typing Techniques; genotyp; Genetic Variation; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization